2005
DOI: 10.1007/s10751-006-9279-4
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the 57Fe quadrupole splitting in the heme models of α- and β-subunits in tetrameric deoxyhemoglobin

Abstract: Ab initio X! discrete variation method was used for calculation of quadrupole splitting for the rough heme models in !-and β-subunits of tetrameric deoxyhemoglobin accounting small stereochemical variations. The differences of theoretical values of quadrupole splitting for these heme models were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…As a result, we have calculated atomic orbital populations (n i ), interatomic atom-atom type overlap population (P), effective charges (Q) and magnetic moments (MM) of atoms, as well as model densities of electronic states (DOS). Calculation details of the electronic structure, chemical bonding and 57 Fe quadrupole splitting used in this work corresponded to those reported in [3,4].…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, we have calculated atomic orbital populations (n i ), interatomic atom-atom type overlap population (P), effective charges (Q) and magnetic moments (MM) of atoms, as well as model densities of electronic states (DOS). Calculation details of the electronic structure, chemical bonding and 57 Fe quadrupole splitting used in this work corresponded to those reported in [3,4].…”
Section: Methodsmentioning
confidence: 97%
“…clusters of neighboring surrounding of Fe 2+ ions in the models I-III of active sites of the α-subunit of oxyhemoglobin [7] Watson sphere [8] Earlier it was shown that the type of local metal-nitrogen chemical bonding is of great importance for the AS of deoxyhemoglobin because the temperature structure stability loss of the AS of α-and β-subunits of deoxyhemoglobin were calculated to be 89 • C, 42 • C, 41 • C, 40 • C, 37 • C, 33 • C, 29 • C for Cr, Mn, Fe, Co, Ni, Cu, Zn, respectively [3]. Besides, temperature dependence of 57 Fe quadrupole splitting corresponding to the active sites of α-and β-subunits of deoxyhemoglobin and deoxymyoglobin were calculated using the first-principle X α -discrete variation method [4]. In this work, we report the results of calculation of 57 Fe quadrupole splitting E Q for the AS of α-and β-subunits of oxyhemoglobin within three models of calculation: without extra electron and in spin-unrestricted mode (model I); without extra electron and in spin-restricted mode (model II); with extra electrons in spin-unrestricted mode (model III).…”
Section: Introductionmentioning
confidence: 99%